The Effect of Perceived Quality, Perceived Sacrifice and Perceived Risk on Customers’ Perception of Product Value for Electronic Product - Muh. Said; Mustaking Mustaking (Universitas Negeri Makassar, 2020)
Now days, retailer always make a new marketing strategy to keep their customers needs, so the customer will be satisfied with their product. Customers ’ perception for product value usually involving the effect of perceived quality, perceived sacrifice and perceived risk and perceived quality. The objectives of this research was to know whether perceived quality, perceived sacrifice and perceived risk has an effect on customer perception of product value for electronic product. The data were collected from 98 respondents. These respondents has bought electronic product in the previous year. The hypothesized relationship was tested using multiple regression analysis. The analysis showed that country of origin, store name, brand name and price has a positive effect to quality, but price doesn’t have a positive effect to perceived sacrifice and also performance risk and perceived risk has a positive effect to financial risk. Another analysis showed that perceived quality doesn’t have a negative effect to performance risk and also performance risk and financial doesn't have a negative effect to perceived value.